Pengembangan Perangkat Asesmen Autentik Keterampilan Menulis Kelas VII dalam Implementasi Kurikulum 2013 - Kasmadi Kasmadi; Titik Harsiati; Nurhadi Nurhadi (Jurnal Pendidikan Humaniora, 2016)
Abstract: This research aims to develop the authentic assessment of writing skills class VII in the implementation of Curriculum 2013, which includes a Free Assessment Task Authentic Authentic Writing and Writing. The method used is a model Reflective, Recursive Desaign and Development (R2D2) and Authentic Assessment model of O’Malley and Pierce with three main stages, namely: (1) pre-development stage, (2) development, and (3) test product. The result, in general, Authentic Assessment Guide Writing and Writing Task Autentik very worthy and ready for use. Results of the assessment experts and practitioners represents an average of 88.67%. Results of the assessment experts and practitioners to Task Authentic Writing Text Reports Observations, showed an average 89.33%, Authentic Writing Task 89.61% Description Text, Text Writing Task Authentic Exposition 91.16%, Authentic Writing Task explanatory text 91, 27%, and Tasks Text Authentic Writing Short Stories 91.16%. Key Words: assessment instrument, text, writting